4G/5G Polymorphism of PAI-1 Gene Promoter and Fibrinolytic Capacity in Patients with Deep Vein Thrombosis - Sartori, Maria Teresa; Wiman, Björn; Vettore, Silvia; Dazzi, Francesco; Girolami, Antonio; Patrassi, Giovanni Maurizio (Thrombosis and Haemostasis, 1998)
A deletion/insertion polymorphism (4G or 5G) in the promoter of the plasminogen activator inhibitor type 1 gene has been suggested to be involved in regulation of the synthesis of the inhibitor, the 4G allele being associated with enhanced gene expression. A relationship between 4G/5G polymorphism and PAI-1 levels was found in patients with cardiovascular and metabolic diseases, but not in healthy subjects. In the present work we studied the distribution of PAI-1 4G/5G geno-type and its relation to fibrinolytic capacity in 70 unrelated patients with deep vein thrombosis. Each patient was assayed before and after 20 min. Venous occlusion for euglobulin lysis time, t-PA antigen and activity, and PAI-1 antigen and activity. The prevalence of 5G homozygous carriers was significantly lower in patients than in controls (10% vs. 26%, p = 0.009). The 5G allele frequency was reduced, even though not significantly, in DVT patients compared to healthy subjects (0.40 vs. 0.51, respectively). In the patient group, the mean PAI-1 antigen and activity levels were significantly higher than among controls and related to the 4G/5G polymorphism. In patients with 4G/5G and 4G/4G genotype a significant correlation was found between PAI-1 levels and the global fibrinolytic activity as evaluated by euglobulin lysis time. The prevalence of a reduced fibrinolytic potential due to PAI-1 excess was 45.7% among DVT patients. Moreover, the prevalence of PAI-1 induced hypofibrinolysis was strongly related to PAI-1 polymorphism, since it was significantly lower in 5G homo-zygous patients (28.6%) than in both 4G/5G carriers (55.3%, p <0.001) and 4G homozygous patients (57.9%, p <0.001).In conclusion, in patients with deep vein thrombosis the 4G polymorphism of PAI-1 gene promoter may influence the expression of PAI-1 and it should be taken into consideration as a facilitating condition for pathological fibrinolysis together with other environmental and genetic factors. Whether this has any significance in regard to the pathogenesis of venous thrombosis remains to be proven.